2021
DOI: 10.3389/fphys.2021.641461
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Rest-Activity Circadian Rhythm in Patients With Metabolic Syndrome

Abstract: Rest-Activity circadian Rhythm (RAR) can be used as a marker of the circadian timing system. Recent studies investigated the relationship between irregular circadian rhythms and cardiovascular risk factors such as hypertension, obesity, and dyslipidemia. These factors are related to the Metabolic Syndrome (MS), a clustering of metabolic risk factors that increases the risk of several cardiovascular and metabolic diseases. This cross-sectional analysis aimed to explore the RAR characteristics by actigraphy in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As individuals tend to underreport their weight and over-report their height (39), BMI generated from self-reported measures may be inaccurate, leading to misclassifications and potentially biasing the association between RAR and obesity. Analysis of baseline data of a randomized trial of 97 patients with metabolic syndrome showed that, of all RAR metrics analyzed, only amplitude was inversely correlated with BMI in women, possibly because of the strict inclusion and exclusion criteria and the small sample size (40). Sohail et al (23) assessed the relationship between RAR stability (IS) and metabolic syndrome in the very elderly and found that low IS was associated with increased risk of BMIbased general obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As individuals tend to underreport their weight and over-report their height (39), BMI generated from self-reported measures may be inaccurate, leading to misclassifications and potentially biasing the association between RAR and obesity. Analysis of baseline data of a randomized trial of 97 patients with metabolic syndrome showed that, of all RAR metrics analyzed, only amplitude was inversely correlated with BMI in women, possibly because of the strict inclusion and exclusion criteria and the small sample size (40). Sohail et al (23) assessed the relationship between RAR stability (IS) and metabolic syndrome in the very elderly and found that low IS was associated with increased risk of BMIbased general obesity.…”
Section: Discussionmentioning
confidence: 99%
“…( 23 ) assessed the relationship between RAR stability (IS) and metabolic syndrome in the very elderly and found that low IS was associated with increased risk of BMI-based general obesity. Of note, these previous studies ( 22 , 23 , 38 , 40 ) evaluated RAR in relation to excess body fat only as expressed by BMI. Abdominal obesity, defined according to waist circumference or waist-to-hip ratio, is an indicator of visceral fat accumulation ( 41 ) and is a more powerful predictor of chronic diseases and premature death than BMI ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physical activity, a more active daily routine and an increment in daily activity levels have been associated with better sleep quality ( 20 ). However, little attention has been given to the daily activity evaluated by RAR in people with MS ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dissonance of the biological clock and endocrine is the primary cause of circadian rhythm disorders. When dysfunctions occur, physiological and pathological disorders such as MetS, cardiovascular diseases, and neuropsychiatric disorders may develop ( 11 , 20 ). All of these factors mentioned above can contribute to TD development ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%